Effects of modafinil on cognitive performance during 40 hr of sleep deprivation in a warm environment. - Baranski JV; Gil V; McLellan TM; Moroz D; Buguet A; Radomski M (Military Psychology, 2002)
This study examined the effect of the psychostimulant modafinil on cognitive performance during 40 hr of sleep deprivation in a warm environment. Five men were randomly assigned to a modafinil (3 x 100 mg/24 hr) and a placebo trial on consecutive weeks, with a 5-day intervening 'wash-out' period. Each trial involved a thermoneutral control day (outside of the climatic chamber) followed by a 40-hr sleep deprivation period in a climatic chamber at 30° C with 50% relative humidity. Ten cognitive testing sessions were conducted on each trial; each session lasted approximately 45 min, and they occurred at 6-hr intervals. The task battery included subjective assessments of mood, fatigue, and motivation and cognitive assessments of serial reaction time, logical reasoning (logical reasoning task [LRT]), visual comparison (CMP), mental addition (ADD), vigilance (detection of repeated numbers [DRN]), and multitasking. In addition, for 4 of the cognitive tasks that permitted a quantitative index of response accuracy (i.e., LRT, CMP, DRN, and ADD), participants provided estimates of their performance before and after each session to permit an evaluation of the extent to which they could accurately self-monitor their own cognitive abilities. The findings revealed that (a) despite significant increases in core body temperature, cognitive performance was largely unaffected by the warm environment per se; (b) sleep loss induced a general reduction in cognitive performance that was largely but not completely eliminated by modafinil; and (c) participants were able to accurately self-monitor their own cognitive capabilities during both the placebo and modafinil trials. In this article, we discuss the potential utility of modafinil in sustained military operations and the general implications of these findings for Hancock's (1986) theory of sustained attention under thermal stress.